Gasification of napier grass and napier grass-oil palm frond blending in a fluidized bed gasifier - Tan, Hong Boon (2017)
To date, oil palm is still the major biomass in Malaysia, thus this provides a strong reason why palm-based biomasses are one of the most promising renewable energy resources for electricity generation. In recent decade, palm-based biomasses have been greatly converted into various types of value-added products other than energy feedstock for power generation. Therefore, alternative fuel resources should be explored to replace palm-based biomasses to avoid over dependent on a single source. In this study, napier grass (Pennisetum pupureum) (NG) is chosen as the feedstock due to its availability and high growth rates. In a year, NG is able to produce 40 tons/ hectare of dry biomass yield which is significantly higher than other short rotation grasses. In addition, the high volatility characteristic of NG makes it a suitable feedstock for thermo-chemical conversion. On the other hand, oil palm frond (OPF) is another suitable feedstock material for thermo-chemical conversion mainly because of its’ availability and high volatility characteristic. Hence, it is blended with NG for performance enhancement. Gasification is chosen as the process to turn NG and NG-OPF blends into syngas due to its simplicity, performance efficiency and less pollutants emission. The physicochemical properties of NG and OPF were determined by Thermogravimetric Analysis (TGA) and Carbon-Hydrogen-Nitrogen-Sulphur (CHNS) characterization. The experimental tests have been carried out in a heat resistant stainless steel fluidized bed reactor (internal diameter 370 mm, length 54 mm) under temperature (650 – 850 °C) and equivalence ratio (0.2 – 0.4). The results revealed that the temperature and ER have significant effect on syngas quality and gasification performance. The higher heating value (HHV) based on the syngas composition obtained experimentally was 3.37 MJ/Nm3 and the higher Carbon Conversion Efficiency (CCE) was 82.12 % at temperature 850 °C with ER 0.25. For ER, the HHV was 3.37 MJ/Nm3 at ER 0.20 and the higher CCE was 89.08 % at ER 0.40. Moreover, the effect of NG-OPF blending ratio (25: 75, 50: 50, 75: 25) on the syngas composition and gas performance were also investigated under optimum condition (ER 0.20 and temperature 850°C). NG-OPF (50: 50) was found to obtained a higher H2 (13.04 mol.%) and higher HHV of gas product (3.42 MJ/kg). In order to generate reasonable prediction of the syngas composition and optimize the H2 production, a gasification model was developed based on the experimental data via LINGO software. In addition, syngas compositions obtained experimentally are validated with gasification modeling. Furthermore, the composition of syngas can be further optimized and determined based on the operating conditions (temperature, ER). The experimental result showed a very good agreement with the predicted result from the model at optimum condition and the RMS was calculated to be 0.0383. Therefore, it can be concluded that NG has the potential to be an alternative sustainable energy fuel for energy generation.